2018
DOI: 10.1177/0145721718777855
|View full text |Cite
|
Sign up to set email alerts
|

Integration and Utilization of Peer Leaders for Diabetes Self-Management Support: Results From Project SEED (Support, Education, and Evaluation in Diabetes)

Abstract: Purpose The purpose of the study was to evaluate the effectiveness of a peer leader-led (PL) diabetes self-management support (DSMS) group in achieving and maintaining improvements in A1C, self-monitoring of blood glucose (SMBG), and diabetes distress in individuals with diabetes. Diabetes self-management support is critical; however, effective, sustainable support models are scarce. Methods The study was a cluster randomized controlled trial of 221 people with diabetes from 6 primary care practices. Practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Peer leaders can play leading, interactive, and cohesive roles and can improve the atmosphere of a peer support module. Internet-based mentoring programs can increase the frequency of blood sugar monitoring [ 46 ], and studies have demonstrated that peer leaders can provide effective diabetes self-management support [ 47 , 48 ]. However, exchanges in current diabetes apps all take the form of forums, which is inconvenient.…”
Section: Discussionmentioning
confidence: 99%
“…Peer leaders can play leading, interactive, and cohesive roles and can improve the atmosphere of a peer support module. Internet-based mentoring programs can increase the frequency of blood sugar monitoring [ 46 ], and studies have demonstrated that peer leaders can provide effective diabetes self-management support [ 47 , 48 ]. However, exchanges in current diabetes apps all take the form of forums, which is inconvenient.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis from this review suggested that culturally tailored DSME interventions involving both trained diabetes educators and peer educators may provide the greatest benefit (9). Peer-led diabetes selfmanagement, a potential low-cost, flexible modality, has been found to successfully maintain key improvements in A1C in rural communities (11,12). Providing bicultural/ bilingual educational materials and involving team members from the community can enhance the cultural sensitivity of DSME programs (13).…”
Section: Dd and Dsme: Literature Reviewmentioning
confidence: 99%
“…Peer support has shown benefits, including social, emotional, and cultural support. 52-55 Various models of peer support exist, with the potential to improve self-efficacy, positive mood, understanding of self-care, and perception of social support as well as improve health-related outcomes. 56 People living with chronic disease are not the only ones who may require this support; family members, caregivers, and partners of people with diabetes can experience diabetes distress.…”
Section: Examination and Validation Of The Adces7mentioning
confidence: 99%